Dynamic Profile of CD4+ T-Cell-Associated Cytokines/Chemokines following Murine Myocardial Infarction/Reperfusion. (18th March 2019) - Yuan, Dongsheng; Tie, Jinjun; Xu, Zhican; Liu, Guanya; Ge, Xinyu; Wang, Zhulin; Zhang, Xumin; Gong, Shiyu; Liu, Gang; Meng, Qingshu; Lin, Fang; Liu, Zhongmin; et al.
Abstract : CD4 + T-cells play crucial roles in the injured heart. However, the way in which different CD4 + T subtypes function in the myocardial infarction/reperfusion (MI/R) heart is still poorly understood. We aimed to detect the dynamic profile of distinct CD4 + subpopulation-associated cytokines/chemokines by relying on a closed-chest acute murine MI/R model. The protein levels of 26 CD4 + T-cell-associated cytokines/chemokines were detected in the heart tissues and serum of mice at day 7 and day 14 post-MI/R or sham surgery. The mRNA levels of IL-4, IL-6, IL-13, IL-27, MIP-1 β, MCP-3, and GRO- α were measured in blood mononuclear cells. The protein levels of IL-4, IL-6, IL-13, IL-27, MIP-1 β, MCP-3, and GRO- α increased in both injured heart tissues and serum, while IFN- γ, IL-12P70, IL-2, IL-1 β, IL-18, TNF- α, IL-5, IL-9, IL-17A, IL-23, IL-10, eotaxin, MIP-1 α, RANTES, MCP-1, and MIP-2 increased only in MI/R heart tissues in the day 7 and day 14 groups compared to the sham group. In serum, the IFN- γ, IL-23, and IL-10 levels were downregulated in the MI/R model at both day 7 and day 14 compared to the sham. Compared with the protein expressions in injured heart tissues at day 7, IFN- γ, IL-12P70, IL-2, IL-18, TNF- α, IL-6, IL-4, IL-5, IL-9, IL-17A, IL-23, IL-27, IL-10, eotaxin, IP-10, RANTES, MCP-1, MCP-3, and GRO- α were reduced, while IL-1 β and MIP-2 were elevated at day 14. IL-13 and MIP-1 β showed higher levels in the MI/R serum at day 14 than at day 7. mRNA levels of IL-4, IL-6, IL-13, and IL-27 were increased in the day 7 group compared to the sham, while MIP-1 β, MCP-3, and GRO- α mRNA levels showed no significant difference between the MI/R and sham groups in blood mononuclear cells. Multiple CD4 + T-cell-associated cytokines/chemokines were upregulated in the MI/R hearts at the chronic stage. These results provided important evidence necessary for developing future immunomodulatory therapies after MI/R.